Analytical calculation of the lower bound on timing resolution for PET scintillation detectors comprising high-aspect-ratio crystal elements. (17th June 2015) - Cates, Joshua W; Vinke, Ruud; Levin, Craig S
Abstract: Excellent timing resolution is required to enhance the signal-to-noise ratio (SNR) gain available from the incorporation of time-of-flight (ToF) information in image reconstruction for positron emission tomography (PET). As the detector's timing resolution improves, so does SNR, reconstructed image quality, and accuracy. This directly impacts the challenging detection and quantification tasks in the clinic. The recognition of these benefits has spurred efforts within the molecular imaging community to determine to what extent the timing resolution of scintillation detectors can be improved and develop near-term solutions for advancing ToF-PET. Presented in this work, is a method for calculating the Cramér–Rao lower bound (CRLB) on timing resolution for scintillation detectors with long crystal elements, where the influence of the variation in optical path length of scintillation light on achievable timing resolution is non-negligible. The presented formalism incorporates an accurate, analytical probability density function (PDF) of optical transit time within the crystal to obtain a purely mathematical expression of the CRLB with high-aspect-ratio (HAR) scintillation detectors. This approach enables the statistical limit on timing resolution performance to be analytically expressed for clinically-relevant PET scintillation detectors without requiring Monte Carlo simulation-generated photon transport time distributions. The analytically calculated optical transport PDF was compared with detailed light transport simulations, and excellent agreement was found between the two. The coincidence timing resolution (CTR) between two mm LYSO:Ce crystals coupled to analogue SiPMs was experimentally measured to be ps FWHM, approaching the analytically calculated lower bound within 6.5%.